Healthcare provider and parent perceptions of newborn care and referral pathways in three hospitals in western Kenya; a formative study - Warren, Charlotte E.; Namai, Irene; Maloba, Florence Thungu; Ogalo, Harriet; Olayo, Bernard; Rochat, Michel; Schönenberger, Klaus; Suter, Silvan; Martin Hilber, Adriane (Frontiers in Pediatrics, 2025)
BackgroundThe common causes of the 1.1 million newborn deaths in sub–Saharan Africa are birth asphyxia and trauma, severe infections, and complications of prematurity. Hypothermia is also a major threat to newborn survival. Three-quarters of newborn deaths could be prevented with essential equipment, skilled neonatal health workers, and a safe neonatal transport referral system. Following a review of the challenges and opportunities in caring for sick newborns, a university department (that develops sustainable and scalable solutions to address unmet needs in low-income settings) is developing an innovative newborn incubator and care solution. As part of a co-design collaborative process between the incubator developers and users, this paper explores the experiences of providers and parents of hospitalized newborns in Kenya.MethodsA qualitative design: in-depth interviews with 19 healthcare providers working in maternity unit, newborn unit, or pediatric ward; interviews with 11 parents/caregivers of hospitalized sick newborn and very young infants (0–60 days), and ethnographic observations conducted in three hospitals in Western Kenya. Data collectors experienced in qualitative methods and newborn health were trained on study topics, interview guides, and research ethics. Interviews were audio-recorded, transcribed verbatim and translated into English. Data were analyzed using NVivo 11 qualitative software.ResultsThe findings are presented around four themes: (1) facility infrastructure and medical supplies, devices for newborn care, and equipment maintenance; (2) characteristics of transfers/referrals of newborns between hospitals- healthcare provider views; (3) healthcare providers’ reports on caring for newborns, provider, skills, and competency in newborn care; and (4) Parents’ experiences during transfer and hospitalization of their small or sickcaring for a hospitalized baby.ConclusionHypothermia continues to be a problem for newborns, especially in primary healthcare settings and transfers between facilities. Potential interventions include a review of provider newborn skills and updates, including Kangaroo Mother Care, addressed through existing mentoring programs. Essential thermal equipment is also required to support quality care of small and sick newborns, including for inter and intra-facility transfers. An increased focus on providing quality thermal care of small and sick newborns is warranted.